"Not our class darling": networking – privilege or penalty in large hotels?. Issue 2 (13th December 2019) - Ryan, Irene; Mooney, Shelagh Karin
Abstract : Purpose: The purpose of this paper is to show how the social categories of gender, age and class influence networking practices and career progression in the 4–5-star hotel sector in Australia and New Zealand. It argues that in this type of workplace the practice of networking is so normalized that it is assumed an inclusive, gender-neutral activity. Design/methodology/approach: This paper draws on 18 semi-structured interviews. Inductive analysis was used uncover themes, sub-themes and emergent patterns. An intersectionally sensitive approach was followed. Findings: The significance of networking processes for career progression in the 4–5-star hotel sectors was a recurring theme. Networking reflects historically embedded gendering practices that heighten existing class-based structural privilege for groups of men. Research limitations/implications: The focus is on hotel employees in Australia and New Zealand with the findings are not implicitly generalizable. Practical implications: Networks are important for women as their "merit" may not be immediately visible. Well-structured mentoring schemes need to be adopted as part of the affirmative action required to tilt the "skewed playing field". Originality/value: Studies that indicate how the gendering of networking practices reinforce career privilege and penalty in specific organizations have been lacking, as have studies favouring an intersectional approach. This study seeks to redress these omissions.